Proceedings of the 22nd International Conference on Program Comprehension 2014
DOI: 10.1145/2597008.2597152
|View full text |Cite
|
Sign up to set email alerts
|

An empirical comparison of static and dynamic type systems on API usage in the presence of an IDE: Java vs. groovy with eclipse

Abstract: Several studies have concluded that static type systems offer an advantage over dynamic type systems for programming tasks involving the discovery of a new API. However, these studies did not take into account modern IDE features; the advanced navigation and code completion techniques available in modern IDEs could drastically alter their conclusions. This study describes an experiment that compares the usage of an unknown API using Java and Groovy using the IDE Eclipse. It turns out that the previous finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Sunshine et al [1] found that users of Plaiddoc, which documents type state, could answer state search questions faster than users of Javadoc. Mayer et al [2] and Petersen et al [3] found that static type declarations improved performance on some programming tasks and degraded it on others, generally finding that static types are helpful for understanding documented code and fixing type errors but not for fixing semantic errors. However, a more focused look is needed at the tradeoffs involved specifically in type declarations and their longer-term effects.…”
Section: Introductionmentioning
confidence: 99%
“…Sunshine et al [1] found that users of Plaiddoc, which documents type state, could answer state search questions faster than users of Javadoc. Mayer et al [2] and Petersen et al [3] found that static type declarations improved performance on some programming tasks and degraded it on others, generally finding that static types are helpful for understanding documented code and fixing type errors but not for fixing semantic errors. However, a more focused look is needed at the tradeoffs involved specifically in type declarations and their longer-term effects.…”
Section: Introductionmentioning
confidence: 99%